IMPLEMENTASI PENDIDIKAN ANTIKORUPSI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MEMPERKUAT KARAKTER SISWA DI SMP NEGERI 18 SURAKARTA - Agustin, Safira; Sutoyo Sutoyo; Wartoyo Wartoyo (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to describe the implementation of anti-corruption education in Pancasila Education learning at SMP Negeri 18 Surakarta, identify teachers' strategies in instilling anti-corruption values in students, and analyze supporting and inhibiting factors in its implementation. This research used a qualitative approach with a descriptive research design. The research subjects consisted of the school principal, Pancasila Education teachers, and eighth grade students. Data collection techniques included observation, interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing. The results showed that anti-corruption education had been implemented through the cultivation of honesty, discipline, and responsibility values in the learning process. Teachers implemented several strategies such as providing understanding of anti-corruption values, encouraging honest and disciplined behavior, giving independent assignments, and providing role models for students. Supporting factors include teacher commitment and school support in strengthening character education, while inhibiting factors include differences in student character and external environmental influences.